Treatment and utilization of the concentrate from membrane separation processes of landfill leachates - Nowak, Rafał; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the paper was to assess the effectiveness of selected physico-chemical processes to improve the quality of retentates/concentrates obtained during the treatment of landfill leachates using membrane separation. Among the physico-chemical methods, Advanced Oxidation Process (AOP) and electrocoagulation were analysed. Landfill leachate resulting from the infiltration of waste mass by atmospheric precipitation as well as the dissolution and leaching of waste components are most often subjected to membrane separation.
Keywords: landfill leachate; retentate; membrane processes; electrocoagulation; AO